The role of NO in the posterior hypothalamus in amygdala-generated pressor responses in conscious rats - YANANLI, HASAN RACİ; GÖREN, MEHMET ZAFER (My University, 2013)
The nitrergic system modulates cardiovascular functions of the central nucleus of amygdala (CeA) and the posterior hypothalamus (PH) which are involved in the central regulation of the cardiovascular system. The aim of this study was to investigate the contribution of nitric oxide (NO) in the PH in eliciting cardiovascular responses produced through electrical stimulation (ES) of the CeA. Rats were implanted with a stimulation electrode and a parenchymal cannula system into the CeA and a parenchymal cannula or a microdialysis probe into the PH. The next day, the femoral artery was cannulated for haemodynamic measurement. The CeA was electrically stimulated to produce cardiovascular response. The nitric oxide synthetase inhibitor, NG-nitro-L-arginine methyl ester (L-NAME; 400 nmol/100 nl) or artificial cerebrospinal fluid were injected into the PH or the CeA before the ES of the CeA. The dialysates were collected from the PH to determine the L-citrulline and the L-glutamic acid levels. L-NAME injection into the CeA but not to the PH suppressed the increases in the mean arterial pressure produced by the ES of the CeA significantly; however, heart rate was not affected by L-NAME injection into either the PH or the CeA. L-citrulline and L-glutamic acid levels in the PH were shown to be increased by the ES of the CeA. NO is involved between the PH and the CeA which has a considerable role in the central regulation of the cardiovascular system. © 2013 Blackwell Publishing Ltd.
Keywords: Blood pressure; Heart rate; L-citrulline; L-glutamic acid; Microdialysis